The actions of health teams in caring for deaf or hearing-impaired elderly people (Research, Society and Development, 2021)
Aging has been evident in debates aimed at a broad movement of assistance to the elderly, whether in the area of ​​health or in the scope of other public policies. These are subject to rights and need to be guaranteed access to these same rights. Along with aging come adversities such as hearing impairment, which is based on the distinction related to regular ability for the detection of sounds and, mainly, in relation to the individual's resourcefulness, which can be classified according to their location anatomical, be they: conductive, sensory neural, central and functional mixed. Thus, this research originates from the following problem: What are the main actions developed by health teams in caring for the deaf or hearing impaired elderly? The general objective is to analyze the actions developed by the health teams in the care of the deaf or hearing impaired elderly. The study based on an integrative review that is based on research already elaborated on the subject in question, especially through books and scientific articles and whose objective is to group and summarize research results on a demarcated subject, in a systematic and orderly manner, collaborating for that the knowledge about the researched topic be deepened.